ScPdZn and ScPtZn with YAlGe Type Structure – Group‐Subgroup Relation and 45Sc Solid State NMR Spectroscopy1. Issue 2 (20th August 2012) - Hoffmann, Rolf‐Dieter; Mishra, Trinath; Heying, Birgit; Rodewald, Ute Ch.; Matar, Samir F.; Deters, Heinz; Eckert, Hellmut; Pöttgen, Rainer
Abstract The intermetallic compounds ScPdZn and ScPtZn were prepared from the elements by high‐frequency melting in sealed tantalum ampoules. Both structures were refined from single crystal X‐ray diffractometer data: YAlGe type, Cmcm, a = 429.53(8), b = 907.7(1), c = 527.86(1) pm, wR2 = 0.0375, 231 F2 values, for ScPdZn and a = 425.3(1), b = 918.4(2), c = 523.3(1) pm, wR2 = 0.0399, 213 F2 values for ScPtZn with 14 variables per refinement. The structures are orthorhombically distorted variants of the AlB2 type. The scandium and palladium (platinum atoms) build up ordered networks Sc3Pd3 and Sc3Pt3 (boron networks) which are slightly shifted with respect to each other. These networks are penetrated by chains of zinc atoms (262 pm in ScPtZn) which correspond to the aluminum positions, i.e. Zn(ScPd) and Zn(ScPt). The corresponding group‐subgroup scheme and the differences in chemical bonding with respect to other AlB2‐derived REPdZn and REPtZn compounds are discussed. 45Sc solid state NMR spectra confirm the single crystallographic scandium sites. From electronic band structure calculations the two compounds are found metallic with free electron like behavior at the Fermi level. A larger cohesive energy for ScPtZn suggests a more strongly bonded intermetallic than ScPdZn. Electron localization and overlap population analyses identify the largest bonding for scandium with the transition metal (Pd, Pt).